2010
DOI: 10.1029/2009jc005647
|View full text |Cite
|
Sign up to set email alerts
|

Intraseasonal variability in sea surface height over the South China Sea

Abstract: [1] Intraseasonal sea surface height (SSH) variability and associated eddy energy in the South China Sea is studied using satellite observations and an eddy-resolving, global ocean general circulation model. In both the model hindcast and satellite observations, a conspicuous minimum of intraseasonal SSH variance is found along the continental break between the shallow shelf and deep basin. Specifically strong intraseasonal variability (ISV) exists in the following regions: on the northern continental shelf, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
63
0
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 79 publications
6
63
0
3
Order By: Relevance
“…In previous studies, the seasonal signals on velocities are also treated as "eddy" variations, thus the EKE largely reflects a mixture of seasonal mean flows and transient eddies. In contrast, in a recent study focusing on intraseasonal sea level variations in the SCS, "eddy" is defined as the variability on intraseasonal timescale (Zhuang et al, 2010). The latter definition clearly displays two high-energy bands, consistent with the two major eddy pathways revealed in this study.…”
Section: Discussionmentioning
confidence: 51%
See 2 more Smart Citations
“…In previous studies, the seasonal signals on velocities are also treated as "eddy" variations, thus the EKE largely reflects a mixture of seasonal mean flows and transient eddies. In contrast, in a recent study focusing on intraseasonal sea level variations in the SCS, "eddy" is defined as the variability on intraseasonal timescale (Zhuang et al, 2010). The latter definition clearly displays two high-energy bands, consistent with the two major eddy pathways revealed in this study.…”
Section: Discussionmentioning
confidence: 51%
“…This study uses the output of QSCAT run, whose performance is better than the NCEP run because of high resolution and accuracy of the wind forcing 7 (Zhuang et al, 2010). The 3-day snapshots of SSH during 2000-2008 are applied in this study.…”
Section: Product From the Eddy-resolving Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…The analysis of moored buoy data found that there was also a significant period of 40-70 day intraseasonal oscillation in the subsurface near the SCSWBC region [89]. Zhuang et al [90] noted that there existed a weak seasonal signal between 100-and 200-m isobaths in the SCSWBC, which separated the strong intraseasonal signals of shallow and deep waters. We suspect that the intraseasonal variability (ISV) of the WBC cannot be significant in the WBC region because the WBC is a relatively stable and strong flow, but the WBC originated from the Luzon Strait and in Vietnam jet area, due to different dynamic factors and eddies can cause relatively strong ISV signals in these regions.…”
Section: Air-sea Interactionmentioning
confidence: 99%
“…Modeling results by Chu et al [1998] indicated wind effect in generating the SCS deep eddies. By combining the observations and an eddy-resolving model, propagation of eddies and their role in the transport of heat and salt are investigated [Zhuang et al, 2010a;Chen et al, 2012]. Their results indicate the importance of energy exchange between the mean flow and eddies via baroclinic/barotropic instabilities in the SCS.…”
Section: Introductionmentioning
confidence: 99%